Platelet and endothelial cell P‐selectin are required for host defense against Klebsiella pneumoniae‐induced pneumosepsis - Stoppelaar, S. F.; Veer, C.; Roelofs, J. J. T. H.; Claushuis, T. A. M.; Boer, O. J.; Tanck, M. W. T.; Hoogendijk, A. J.; Poll, T. (Journal of thrombosis and haemostasis, 2015)
Summary Background Sepsis is associated with activation of platelets and endothelial cells accompanied by enhanced P‐selectin surface expression. Both platelet‐ and endothelial P‐selectin have been associated with leukocyte recruitment and induction of inflammatory alterations. Klebsiella (K.) pneumoniae is a common human sepsis pathogen, particularly in the context of pneumonia. Methods Wild‐type (WT) and P‐selectin‐deficient (Selp−/−) mice or bone marrow chimeric mice were infected with K. pneumoniae via the airways to induce pneumosepsis. Mice were sacrificed during early (12 h after infection) or late‐stage (44 h) sepsis for analyses, or followed in a survival study. Results Selp−/− mice displayed 10–1000‐fold higher bacterial burdens in the lungs, blood and distant organs during late‐stage sepsis. P‐selectin deficiency did not influence leukocyte recruitment to the lungs, but was associated with decreased platelet‐monocyte complexes and increased cytokine release. Bone marrow transfer studies revealed a role for both platelet and endothelial cell P‐selectin as mice deficient in platelet or endothelial cell P‐selectin displayed an intermediate phenotype in bacterial loads and survival compared with full wild‐type or full knockout control mice. Conclusion Both platelet and endothelial cell P‐selectin contribute to host defense during Klebsiella pneumosepsis.